Peran Fomo dalam Perilaku Konsumen Terhadap Pembentukan Keputusan Konsumtif Perspektif QS Al Hadid Ayat 20 - Amelia, Yesi; Razzaq, Abdur; Nugraha , Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Fenomena Fear of Missing Out (FOMO) is increasingly in the spotlight in the digital era, especially among the younger generation who are active on social media. This research seeks to analyze the phenomenon of FOMO in the context of consumerism through an Islamic perspective, referring to QS Al-Hadid verse 20. Using a qualitative approach, the results show that social media plays an important role in the formation of FOMO, which can trigger impulse buying behavior and increase life dissatisfaction. From an Islamic perspective, consumptive behavior arising from feelings of FOMO contradicts the teachings on modesty and self-control. Therefore, financial education and a deeper understanding of Islamic teachings, especially regarding the concepts of modesty and self-control, are needed to strengthen healthy and wise consumption patterns. This study also emphasizes the importance of preserving wealth (Hifz al-Mal) in accordance with the Maqashid Syariah principle in managing consumptive behavior. Islamic values such as simplicity, gratitude, and self-control can be a provision for individuals to overcome harmful consumptive tendencies. The findings are expected to provide new insights into the relationship between FOMO, social media, and consumptive behavior, and affirm the importance of Islamic principles in maintaining the overall well-being of individuals.